Testican 1 (SPOCK1) and protein tyrosine phosphatase, receptor type S (PTPRS) show significant increase in saliva of tobacco users with oral cancer. (20th September 2018) - Nanjappa, Vishalakshi; Raja, Remya; Radhakrishnan, Aneesha; Jain, Ankit P; Datta, Keshava K; Puttamallesh, Vinuth N; Solanki, Hitendra S; Chavan, Sandip; Patil, Arun; Renuse, Santosh; Jain, Anu; Mathew, Don; et al.
Objectives: To identify potential candidate proteins which are secretory in nature and present at a higher abundance in oral cancer patients with tobacco habits. Methods: Conditioned media of tobacco-treated and -untreated non-neoplastic oral keratinocytes were analyzed using iTRAQ-based mass spectrometry. Hypersecreted proteins; SPARC (osteonectin), cwcv and kazal like domains proteoglycan 1 (SPOCK1); prosaposin (PSAP); and protein tyrosine phosphatase, receptor type S (PTPRS) were validated by enzyme-linked immunosorbent assay (ELISA) using saliva samples from oral cancer patients who are tobacco users. Results: Proteomic analysis of tobacco-treated and -untreated cells led to the identification of 2873 proteins. Among these, 378 proteins showed high abundance and 253 proteins showed low abundance (2-fold cutoff) in conditioned-media of tobacco-treated cells. ELISA-based validation showed significantly higher levels of SPOCK1, PSAP, and PTPRS in oral cancer patients with tobacco chewing habits compared to healthy controls. However, PSAP showed low specificity compared to SPOCK1 and PTPRS. Conclusions: This study indicates significantly increased levels of SPOCK1, PSAP, and PTPRS in saliva of oral cancer patients with tobacco habits. These protein biomarkers might be useful to identify tobacco users with high risk of developing oral cancers.